PENERAPAN M-BANKING DALAM MENINGKATKAN JASA, LAYANAN PERBANKAN DI BANK RAKYAT INDONESIA - Nainggolan, Desi Aminarti; Simanjuntak, Christin Grace; Nainggolan, Yuni Kafrina; Silalahi, Ignatius Valdo; Hutasoit, Naomi Serepina; Hasugian, Christnova; Siallagan, Hamonangan (Jurnal Daya Saing, 2025)
The implementation of m-banking at Bank Rakyat Indonesia is a strategic step to improve service quality and strengthen the relationship between banks and customers. Through innovation in m-banking features, the bank can meet the needs of customers who are increasingly diverse and modern. Digital education and literacy are important aspects to ensure customers understand and utilize m-banking services properly. In addition, customer data security should be a top priority in the development of digital services to build customer trust.